Human kidney stone matrix: Latent potential to restrain COM induced cytotoxicity and inflammatory response. (25th December 2017) - Narula, Shifa; Tandon, Simran; Baligar, Prakash; Singh, Shrawan Kumar; Tandon, Chanderdeep
Abstract: Kidney stone disease is a multi-factorial disorder resulting from the interplay of various risk factors including lifestyle, environment and genetics along with metabolic activities inside the body. However, it is difficult to determine how these factors converge to promote stone disease. Extensive investigations of kidney stone composition at the molecular level have been carried out however; its impact on the complex mechanism of stone formation is still obscure. Hence, an in vitro study was designed to investigate the attenuation of calcium oxalate toxicity by human kidney stone matrix proteins on NRK-52E cells using flowcytometry, Western blotting, RT-PCR and immunofluorescence assays. Morphological alterations in cell-crystal interaction were assessed using scanning electron microscopy. Microscopic studies showed profound impairment of COM crystal structure as a consequence of protein-crystal interactions. RT-PCR analysis and immunocytochemistry of NRK-52E cells revealed the up-regulation of inflammatory and stress biomarkers OPN and HSP-70, respectively, in response to COM toxicity; which diminished significantly in the presence of kidney stone matrix proteins. The results of present study propose that the mechanism undertaken by matrix proteins to attenuate COM induced cytotoxicity could be attributed to the modulation of crystal structure, which subsequently restraint the inflammatory response and apoptotic cell death. The inference drawn through this study could provide better understanding of the intricate process of kidney stone formation. Graphical abstract: Highlights: Kidney stone matrix proteins attenuate COM induced renal cytotoxicity. Matrix proteins downregulate inflammatory as well as stress markers at the gene and protein level in COM injured cells. The plausible key mechanism could be attributed to the modulation of crystal structure.